A comparison of four porewater sampling methods for metal mixtures and dissolved organic carbon and the implications for sediment toxicity evaluations. (26th July 2017) - Cleveland, Danielle; Brumbaugh, William G.; MacDonald, Donald D.
Abstract: Evaluations of sediment quality conditions are commonly conducted using whole‐sediment chemistry analyses but can be enhanced by evaluating multiple lines of evidence, including measures of the bioavailable forms of contaminants. In particular, porewater chemistry data provide information that is directly relevant for interpreting sediment toxicity data. Various methods for sampling porewater for trace metals and dissolved organic carbon (DOC), which is an important moderator of metal bioavailability, have been employed. The present study compares the peeper, push point, centrifugation, and diffusive gradients in thin films (DGT) methods for the quantification of 6 metals and DOC. The methods were evaluated at low and high concentrations of metals in 3 sediments having different concentrations of total organic carbon and acid volatile sulfide and different particle‐size distributions. At low metal concentrations, centrifugation and push point sampling resulted in up to 100 times higher concentrations of metals and DOC in porewater compared with peepers and DGTs. At elevated metal levels, the measured concentrations were in better agreement among the 4 sampling techniques. The results indicate that there can be marked differences among operationally different porewater sampling methods, and it is unclear if there is a definitive best method for sampling metals and DOC in porewater. Environ Toxicol Chem 2017;36:2906–2915. Published 2017 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.